Dinamika Penentuan Dui Papenre’ dalam Perkawinan Adat Suku Bugis di Kalimantan Selatan: Dampak Terhadap Kehormatan Keluarga - Zaidah, Yusna; Mas'ud (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This research delineates the practice of determining dui papenre' in Bugis customary marriages in Tanah Bumbu Regency, South Kalimantan. Dui papenre' is a financial contribution required from the prospective husband for the wedding ceremony, with a relatively high amount. The determination is made by the family of the prospective wife, based on considerations such as the prices of basic commodities, family social status, and the education level of the prospective wife. Its impacts involve marriage postponements, cancellations, and additional burdens for married couples. Nevertheless, this practice also reflects the preservation of family status and honor, especially for the female party, in accordance with prevailing customary traditions. This study explores the social and cultural implications of dui papenre' determination and provides insights into the dynamics of marital relationships in Bugis communities in South Kalimantan. Keywords : Determination, Dui Papenre', Marriage, Bugis Tribe, South Kalimantan Abstrak Penelitian ini menggambarkan praktik penentuan dui papenre’ dalam perkawinan adat Suku Bugis di Kabupaten Tanah Bumbu, Kalimantan Selatan. Dui papenre’ merupakan kontribusi finansial yang harus disiapkan oleh calon suami untuk penyelenggaraan pesta perkawinan, dengan nominal yang relatif tinggi. Penentuan ini dilakukan oleh pihak keluarga calon isteri, berdasarkan pertimbangan harga bahan pokok, status sosial keluarga, dan pendidikan calon isteri. Dampaknya melibatkan penundaan perkawinan, pembatalan, serta beban tambahan bagi pasangan yang telah menikah. Meski demikian, praktik ini juga mencerminkan pemeliharaan status dan kehormatan keluarga, terutama bagi pihak perempuan, sesuai dengan tradisi adat yang berlaku. Studi ini mengeksplorasi implikasi sosial dan budaya dari penentuan dui papenre’ dan memberikan wawasan terhadap dinamika hubungan perkawinan dalam masyarakat Suku Bugis di Kalimantan Selatan. Kata kunci : Penentuan, Dui Papenre’, Perkawinan, Suku Bugis, Kalimantan Selatan This is an open access article under the CC BY-NC-SA license.